Energy‐Resolved Detection of Precipitating Electrons of 30–100 keV by a Sounding Rocket Associated With Dayside Chorus Waves. Issue 3 (8th March 2021) - Sugo, S.; Kawashima, O.; Kasahara, S.; Asamura, K.; Nomura, R.; Miyoshi, Y.; Ogawa, Y.; Hosokawa, K.; Mitani, T.; Namekawa, T.; Sakanoi, T.; Fukizawa, M.; et al.
Abstract: Whistler mode chorus waves scatter magnetospheric electrons and cause precipitation into the Earth's atmosphere. Previous measurements showed that nightside chorus waves are indeed responsible for diffuse/pulsating aurora. Although chorus waves and electron precipitation have also been detected on the dayside, their link has not been illustrated (or demonstrated) in detail compared to the nightside observations. Conventional low‐altitude satellite observations do not well resolve the energy range of 10–100 keV, hampering verification on resonance condition with chorus waves. In this paper we report observations of energetic electrons with energies of 30–100 keV that were made by the electron sensor installed on the NASA's sounding rocket RockSat‐XN. It was launched from the Andøya Space Center on the dayside (MLT ∼ 11 h) at the L‐value of ∼7 on January 13, 2019. Transient electron precipitation was observed at ∼50 keV with the duration of <100 s. The VLF receiver of a ground station at Kola peninsula in Russia near the rocket's footprint observed intermittent emissions of whistler‐mode waves at the VLF frequency range simultaneously with the rocket observations. The energy of precipitating electrons is consistent with those derived from the quasilinear theory of pitch angle scattering by chorus waves through cyclotron resonance, assuming a typical dayside magnetospheric electron density. Precise interaction region is discussed based on the obtained energy spectrum below 100 keV. Plain Language Summary: The Earth's magnetosphere was filled with energetic electrons and various waves. Energetic electrons sometimes precipitate into the Earth's atmosphere and cause aurora. Whistler mode waves are believed to cause such precipitation and previous measurements showed that nightside chorus waves are responsible for aurora. Energetic electrons and chorus waves are also observed on the dayside magnetosphere. However, their link has not been illustrated in detail compared to the nightside observations. In this study, we verified the energy spectrum of precipitating electrons on the dayside by installing the sensor which can resolve the 30–100 keV energy range on a sounding rocket and observed transient electron precipitation. Key Points: We conducted a sounding rocket experiment, which obtained detailed energy spectrum of precipitating electrons of 30–100 keV on the dayside Our sounding rocket experiment identified precipitating energetic electrons within typical resonance energy with chorus waves on the dayside Ground‐based and satellite observations of chorus waves support that the observed electron precipitation was caused by chorus waves